Evaluasi Sistem Informasi Pengetesan Panel Dengan Metode Waterfall Di PT. Schneider Electrik Indonsia - Asep Muhidin; Andriyana Andriyana (Jurnal SIGMA, 2021)
With the increasing market needs since the last few years companies that produce electrical panels LV (Low Voltage), and MV (Medium Voltage). As a large company from France, PTSchneider Electrik Indonesia continues to make improvements in everything, especially in improving its work system, in improving production performance it will always be evaluated both in its work and in its system. In this thesis discusses how to Evaluate the Panel Testing Information System that is able to reduce production errors and reduce delays in work with the Waterfall method and tools for modeling using UML (unifield Modeling Language) and made windows applications developed with vb 2010. The results obtained from a windows application can facilitate quality employees where the panel has been tested or not, no delay in the work or the same panel serial number. And can provide information about errors that occur so that it cannot be repeated. Keywords: data input, UML, Waterfall method